Pyroelectric and Ferroelectric Properties of Hafnium Oxide Doped with Si via Plasma Enhanced ALD - Markus Neuber; Maximilian Walter Lederer; Konstantin Mertens; Thomas Kämpfe; Malte Czernohorsky; Konrad Seidel (Crystals, 2022)
Devices based on ferroelectric hafnium oxide are of major interest for sensor and memory applications. In particular, Si-doped hafnium oxide layers are investigated for the application in the front-end-of-line due to their resilience to high thermal treatments. Due to its very confined doping concentration range, Si:HfO2 layers based on thermal atomic layer deposition often exhibited a crossflow pattern across 300 mm wafer. Here, plasma enhanced atomic layer deposition is explored as an alternative method for producing Si-doped HfO2 layers, and their ferroelectric and pyroelectric properties are compared.